KEKAYAAN JENIS KELELAWAR (CHIROPTERA) DI KAWASAN GUA LAWA KARST DANDER KABUPATEN BOJONEGORO - Nurfitrianto, Hendrik; Budijastuti, Widowati; Faizah, Ulfi (LenteraBio: Berkala Ilmiah Biologi, 2013)
Bats are one of the animals that have the 2nd greatest diversity of species in the class of mammals after Rodentia. One of bats habitat is karst cave. East Java has more karst area like Tuban, Gresik and Bojonegoro. The bats of Lawa Cave at karst Dander have not studied yet. This study aimed to identify the species of bat in area Lawa Cave karst region Dander Bojonegoro. This research conducted during the months of February-March 2013. Bats collected directly from 4 stations in Lawa cave area using traps mistnet with size 3x10 m. Identification was done in the Taxonomy Laboratory Department of Biology UNESA. The results of this study obtained 5 species of bat: Rousettus amplexicaudatus, Hipposideros larvatus, Pipistrellus javanicus, Rhinolophus pusillus, Megaderma spasma.